Sosialisasi Literasi Digital: Peran Perempuan dalam Mendampingi Anak di Kelompok Fatayat - Arnani, Ni Putu Rizky; Rismaningtyas, Fitria; Ni'amah, Luthfi Ulfa (LPPPM STAI Darul Hikmah Bangkalan, 2025)
The unstoppable flow of information can be accessed by children. Parents as the child's closest ecosystem, have an important role to assist in using this technology. This education was provided by the Fatayat Nahdatul Ulama (NU) group in one of the Madiun areas. In order to prevent and solve problems related to the use of gadgets, efforts can be made through increasing community participation through socialization and education as a preventive measure. This program involved 40 Fatayat women. The service program aims to provide knowledge that can ultimately help individuals have awareness of the role of women related to digital literacy. The method of service carried out using lectures and discussions. The results of the service showed that at the end of the activity session participants showed an understanding of the impact of using devices, and awareness that parents know the types of applications on children's devicesa